Managing nitrogen metabolism of animal husbandry and aquaculture could mitigate nitrogen threat in the main cities of Yellow River Delta - Yixuan Bai; Huaqing Li; Bin Chen; Hongyi Xie; Yutao Wang (Cleaner Environmental Systems)
Excessive nitrogen input threatens the ecological health of the Yellow River estuary, with the Main Cities in the Yellow River Delta (MCYRD) facing persistent nitrogen management challenges. Previous studies have lacked a detailed characterization of nitrogen metabolism in estuarine and coastal cities, with limited sector-specific assessments, constraining effective management. Based on urban metabolism theory, this study develops a comprehensive nitrogen metabolism model for MCYRD (2015–2023), refining assessments of nitrogen fluxes from extensive animal husbandry and seawater aquaculture. Results show that nitrogen input to the sea fluctuated around 60 Gg, with aquaculture as the dominant contributor (35.53 %) to surface water and the only productive sector with increasing discharge (+5.28 %), followed by animal husbandry (32.00 %). Among them, seawater aquaculture discharged 234.89 % and 508.11 % more nitrogen than inland aquaculture in Binzhou and Dongying, respectively, posing ecological risks due to the lack of wastewater discharge standards, particularly from shellfish farming. Untreated extensive animal husbandry contributed 81.43 % of animal husbandry runoff, with cattle in Binzhou and sheep in Dongying as the major sources, highlighting the urgency of improved manure management. Meanwhile, by enforcing wastewater treatment in aquaculture, MCYRD could cut nitrogen emissions by 13.00 Gg, while fertilizer reduction and livestock intensification offer long-term mitigation potential. Upgrading wastewater treatment technologies remains essential for sustained nitrogen control. Our findings provide a scientific basis for nitrogen pollution management in MCYRD, supporting targeted strategies for coastal ecosystem protection.